Berakhirnya Kisah Manis Apple dan Samsung: Mengatasi Konflik Organisasi Eksternal Multidimensional dengan Komunikasi Organisasi Efektif - Damanik, Elsye Rumondang; Bambang Mulyono, Damianus Cosmas; Wiratma, Margana; Ndau, Romanus (Humaniora, 2013)
Conflict within an organization could occur in the context of personal communication and group communication. It is not infrequently that multidimensional organizational conflict ultimately affects the performance of a group as a whole. The purpose of this article is to discuss how the role of communication in resolving conflicts organizations external organizations. To focus on the subject matter, the writers conducted a case study discussion by using the concept of multidimensional organizational conflict (implemented in external organizational conflict) in terms of structural, procedural, and situational dimension through effective organizational communication. Yet in this paper, the writers use two dimensions which are procedural and structural dimension. In preparing this paper, the writers undertook a literature study and took a case of Apple and Samsung Electronics in a patent dispute. The results of this study show that effective communication is needed between the organization and its environment; especially competitor organizations which have similar products with different names. Effective organizational communication which could be done is to mediate between organizations. By engaging different means of communication, the exchange of information that occurs between them shall go well.